Cheatgrass (Bromus tectorum L.) management and native plant community recovery on sites selectively treated with Imazapic in Rocky Mountain National Park - Davis, Christopher, author; Brown, Cynthia S., advisor; Paschke, Mark W., committee member; Fernandez-Gimenez, Maria, committee member (Colorado State University. Libraries, 2017)
Cheatgrass, a winter annual grass introduced to North America from Eurasia, has invaded much of the Western United States over the last century. Recently, cheatgrass has become a threat to the montane and subalpine plant communities and ecosystems of Rocky Mountain National Park (RMNP). Cheatgrass aggressively invades disturbed sites and competes with native plant species by rapidly establishing a root system capable of depleting soil moisture and available nitrogen, making cheatgrass control a priority when restoring disturbed areas within RMNP. The purposes of this study were to determine the effectiveness of imazapic for cheatgrass control, its effects on non-target native species, and how the plant community recovers following cheatgrass control. In 2008, 12 permanent monitoring plots were established in six sites in RMNP, each with one reference and one imazapic treatment plot. Reference plots were chosen to represent the desired final condition for each imazapic treatment site. Imazapic (23.6% a.i.) was applied to cheatgrass infestations post-emergence in 2008 (105 g a.i./ha) and pre-emergence in 2009 (105 g a.i./ha) and 2010 (70 g a.i./ha). Imazapic was applied to cheatgrass patches selectively, avoiding application to native species as much as possible. Cheatgrass cover was reduced more than fourfold to approximately 5% in 2013, and there was no decrease in cover of native forbs, grasses, or shrubs. There was no subsequent increase in native species abundance following cheatgrass removal, suggesting further action is needed if the ultimate management goal is to encourage native species recovery in treatment plots after satisfactory cheatgrass control is achieved.
Zip file contains supplementary monitoring materials.